MeCUCC Project: Mindfulness for a holistic education - Gamella González, David (Pulso. Revista de educación, 2016)
The Project MeCUCC, within the framework of the Project QÉREB, derives from a renewed mission of the University Center Cardenal Cisneros. The main objective of this project, built upon the concept of full awareness, is to develop the link between inner observation and external understanding in order to optimize the responsiveness towards the available educational resources, as well as to contribute more effectively to the educational process of the students. The CUCC is fully aware of the need to prepare people to become active agents in social transformation, understanding that in the educational process it is necessary to go beyond the mere transmission of content and skills. The proposed path to achieve this is the promotion of awareness and critical thinking, self-observation, holistic understanding and empathy, as well as collaborative ability and creativity. These are key resources that predispose us as citizens to get involved in achieving a more efficient, fair, friendly and supportive XXI century society